1999
DOI: 10.1007/s11745-999-0435-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, separation, and confirmation of the eight geometrical cis/trans conjugated linoleic acid isomers 8,10‐through 11,13–18∶2

Abstract: Conjugated linoleic acid (CLA) mixtures were isomerized with p-toluenesulfinic acid or I2 catalyst. The resultant mixtures of the eight cis/trans geometric isomers of 8,10-, 9,11-, 10,12-, and 11,13-octadecadienoic (18:2) acid methyl esters were separated by silver ion-high-performance liquid chromatography (Ag+-HPLC) and gas chromatography (GC). Ag+-HPLC allowed the separation of all positional CLA isomers and geometric cis/trans CLA isomers except 10,12-18:2. However, one of the 8,10 isomers (8cis, 10trans-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 11 publications
(28 reference statements)
3
80
0
Order By: Relevance
“…Conjugated linoleic acid, briefly known as CLA, is a mixture of geometrical and positional isomers of linoleic acid (C18:2 c-9, c-12) and involves a double bond at positions 8 and 10, 9 and 11, 10 and 12 or 11 and 13 (Eulitz et al, 1999). Each of these positional conjugated diene isomers can occur in cis-trans, transcis, cis-cis or trans-trans geometrical configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated linoleic acid, briefly known as CLA, is a mixture of geometrical and positional isomers of linoleic acid (C18:2 c-9, c-12) and involves a double bond at positions 8 and 10, 9 and 11, 10 and 12 or 11 and 13 (Eulitz et al, 1999). Each of these positional conjugated diene isomers can occur in cis-trans, transcis, cis-cis or trans-trans geometrical configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2A shows the separation of CLA methyl esters prepared from sunflower oil, on a CP Sil88 column. The GC order of elution of the different CLA isomers is now well documented [3,29]. The GC analysis revealed that the 9,11-and the 10,12-18:2 were the major isomers.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature was held at 170°C for 40 min. The peak identification was carried out by comparing the reported conjugated linoleic acid profiles in references [10,11,13,14] and methyl esters prepared from the 9c11t and 10t12c triacylglycerols as described in the section ''Samples and methods''. The peaks in the chromatograms were then integrated, and their relative percentages were calculated using an excel spread sheet.…”
Section: Gas Chromatographic Analysismentioning
confidence: 99%
“…The two important CLAs namely 9c11t and 10t12c were prepared in large quantities by alkali isomerisation of 9c12c linoleic acid [14]. Eulitz et al [14] synthesised eight CLA isomers, 8,10 through 11,13, by isomerising CLA mixtures by p-toluene sulfinic acid or iodine catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation